ACCOUNTING INFORMATION, NON-ACCOUNTING INFORMATION AND LENDING DECISION - Mariana, Mariana; Abdullah, Syukriy; Nadirsyah, Nadirsyah (Universitas Muhammadiyah Malang)
This study aims to examine the effect of accounting information and non-accounting information on lending decisions on banking institutions in Pidie Jaya Regency, which amounted to 6 (six) banks for the period January 2014-February 2015. The data analyzed were debtor data using multiple linear regression. The results show that return on net worth, debt to equity ratio, and non-accounting information have a significant effect, while fixed assets turn over does not affect the lending decision in Pidie Jaya Regency.